Decreased Pain Perception by Unconscious Emotional Pictures - Peláez, Irene; Martínez-Iñigo, David; Barjola, Paloma; Cardoso, Susana; Mercado, Francisco (Frontiers in Psychology, 2016)
Pain perception arises from a complex interaction between a nociceptive stimulus and different emotional and cognitive factors, which appear to be mediated by both automatic and controlled systems. Previous evidence has shown that whereas conscious processing of unpleasant stimuli enhances pain perception, emotional influences on pain under unaware conditions are much less known. The aim of the present study was to investigate the modulation of pain perception by unconscious emotional pictures through an emotional masking paradigm. Two kinds of both somatosensory (painful and non-painful) and emotional stimulation (negative and neutral pictures) were employed. Fifty pain-free participants were asked to rate the perception of pain they were feeling in response to laser-induced somatosensory stimuli as faster as they can. Data from pain intensity and reaction times were measured. Statistical analyses revealed a significant effect for the interaction between pain and emotional stimulation, but surprisingly this relationship was opposite to expected. In particular, lower pain intensity scores and longer reaction times were found in response to negative images being strengthened this effect for painful stimulation. Present findings suggest a clear pain perception modulation by unconscious emotional contexts. Attentional capture mechanisms triggered by unaware negative stimulation could explain this phenomenon leading to a withdrawal of processing resources from pain.